2020
DOI: 10.1167/tvst.9.9.9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging and the Retina: Worth the Wave?

Abstract: Purpose: Hyperspectral imaging is gaining attention in the biomedical field because it generates additional spectral information to study physiological and clinical processes. Several technologies have been described; however an independent, systematic literature overview is lacking, especially in the field of ophthalmology. This investigation is the first to systematically overview scientific literature specifically regarding retinal hyperspectral imaging. Methods: A systematic literature review was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 104 publications
(328 reference statements)
1
13
0
Order By: Relevance
“…Hyperspectral (HS) imaging has also been used to identify retinal Ab based on spectral shifts in the scattering of light. The retina is illuminated with varying bandwidths of visible to near infrared light, and reflected light is analyzed to determine reflectance intensity at each wavelength, as well as spatial information based on light scattering at each pixel (35,36). Although HS imaging cannot visualize Ab directly, alterations in the reflected light spectra are believed to be caused by the Rayleigh light-scattering properties of small soluble Ab oligomers.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Hyperspectral (HS) imaging has also been used to identify retinal Ab based on spectral shifts in the scattering of light. The retina is illuminated with varying bandwidths of visible to near infrared light, and reflected light is analyzed to determine reflectance intensity at each wavelength, as well as spatial information based on light scattering at each pixel (35,36). Although HS imaging cannot visualize Ab directly, alterations in the reflected light spectra are believed to be caused by the Rayleigh light-scattering properties of small soluble Ab oligomers.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…20 Image analysis methods, including artificial intelligence, are used to detect disease biomarkers. 21 Retinal hyperspectral imaging is a relatively recent advance and it is not yet used in the clinic.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…One of these techniques is hyperspectral retinal imaging, with wavelengths between 460 nm and 570 nm being the most interesting to use. 4,5 Post-mortem studies in both animal and human retinas, and in vivo studies in rodents, have shown that hyperspectral retinal imaging can detect spectral changes that could be caused by the presence of retinal Ab aggregates. 4,6 Hyperspectral retinal imaging, however, does not directly visualise retinal Ab deposition, but records a spectral shift at wavelengths between 460 nm and 570 nm that could be explained by the presence of retinal protein deposits in certain stages of aggregation, given the relationship between particle size and different types of light scattering.…”
Section: Alzheimer's Disease and Its Biomarkersmentioning
confidence: 99%